HIV and Sexually Transmitted Infections in the Netherlands in 2004 : an update - van de Laar, M.J.W.; de Boer, I.M.; Koedijk, F.D.H.; Op de Coul, E.L.M. (Bilthoven : RIVM, 2005)
Fonds Suzan Daniel (FSD)
Engels
Monografie